Infernal discourse of prose by Leonid Andreev - Гомон, Андрій Михайлович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Despite the fact that since the middle of the last century, Andrei has been developing at a rapid pace, many facets of the writer’s work remain «in the background». To a sufficient extent this is also characteristic of the coverage of Andreev’s demonology. Infernal character – a figure of supernatural origin, personifying evil, destructive principle, the term «infernal» is used along with the definition of «demonic». A significant part of the prose work of L. Andreev can be considered as a kind of original «devil» («hoffmaniad»). These are works on the temptation of the «superhuman» («devilish») reason of man («The Story of Sergey Petrovich» (1900), «Thought» (1902), «Darkness» (1907), «My Notes» (1908), etc. ) and works on the themes of the devil («Something about the Devils» (1901), «About the Writer» (1902), «Peace» (1911), «Rules of Good» (1912), «Diary of Satan» (1919)). Some of them are narratives, as if narrated by the devil («It Was» (1905), «Ben-Tovit» (1905), «Eleazar» (1906), «Judas Iscariot» (1907), «Witness of Truth» («Miraculous Image») (1915) and others); others are stories in which the devil himself is a protagonist («Peace» (1911), «Rules of Good» (1912), «Damn at a Wedding» (1915), «Diary of Satan» (1919), etc.); the third – in which human heroes, combining the «superman» and «devil» and non-infernal in origin, take the place of carriers of destructiveness, i.e. – infernal heroes (Ivan Koprov – «The Life of Vasily Thebes» (1903), «grandfather» – «My Notes» (1908), Norden – «He (The Story of the Unknown)» (1913), Thomas Magnus – «The Diary of Satan» (1919 )). In the late work of the writer, the Andreev infernal theme undergoes a significant transformation. If at the beginning of creativity it was a devil testing a person, then in the future the writer’s imagination occupied the paradoxically ridiculous image of a devil who wants to do good. Throughout the career of L. Andreev, in his prose, ironic demonological discourse continued to function, which is of great importance and plays an important role in understanding the entire work of the writer as a whole. He allowed L. Andreev to pose the «damned questions» of human life, comprehending them from an anti-didactic point of view, as well as resist the latest ideas of Nietzscheanism, positivism and God-seeking, so widespread at the beginning of the twentieth century.